Effect of Dopamine D(2) Receptor Antagonists on [(18)F]-FEOBV Binding - Schildt, Anna (Mol Pharm, 2020)
[Image: see text] The interaction of dopaminergic and cholinergic neurotransmission in, e.g., Parkinson’s disease has been well established. Here, D(2) receptor antagonists were used to assess changes in [(18)F]-FEOBV binding to the vesicular acetylcholine transporter (VAChT) in rodents using positron emission tomography (PET). After pretreatment with either 10 mg/kg haloperidol, 1 mg/kg raclopride, or vehicle, 90 min dynamic PET scans were performed with arterial blood sampling. The net influx rate (K(i)) was obtained from Patlak graphical analysis, using a metabolite-corrected plasma input function and dynamic PET data. [(18)F]-FEOBV concentration in whole-blood or plasma and the metabolite-corrected plasma input function were not significantly changed by the pretreatments (adjusted p > 0.07, Cohen’s d 0.28–1.89) while the area-under-the-curve (AUC) of the parent fraction of [(18)F]-FEOBV was significantly higher after haloperidol treatment (adjusted p = 0.022, Cohen’s d = 2.51) than in controls. Compared to controls, the AUC of [(18)F]-FEOBV, normalized for injected dose and body weight, was nonsignificantly increased in the striatum after haloperidol (adjusted p = 0.4, Cohen’s d = 1.77) and raclopride (adjusted p = 0.052, Cohen’s d = 1.49) treatment, respectively. No changes in the AUC of [(18)F]-FEOBV were found in the cerebellum (Cohen’s d 0.63–0.74). Raclopride treatment nonsignificantly increased K(i) in the striatum 1.3-fold compared to control rats (adjusted p = 0.1, Cohen’s d = 1.1) while it reduced K(i) in the cerebellum by 28% (adjusted p = 0.0004, Cohen’s d = 2.2) compared to control rats. Pretreatment with haloperidol led to a nonsignificant reduction in K(i) in the striatum (10%, adjusted p = 1, Cohen’s d = 0.44) and a 40–50% lower K(i) than controls in all other brain regions (adjusted p < 0.0005, Cohen’s d = 3.3–4.7). The changes in K(i) induced by the selective D(2) receptor antagonist raclopride can in part be quantified using [(18)F]-FEOBV PET imaging. Haloperidol, a nonselective D(2)/σ receptor antagonist, either paradoxically decreased cholinergic activity or blocked off-target [(18)F]-FEOBV binding to σ receptors. Hence, further studies evaluating the binding of [(18)F]-FEOBV to σ receptors using selective σ receptor ligands are necessary.